2013
DOI: 10.1093/jac/dkt123
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of extended-spectrum- -lactamase-producing Escherichia coli isolates collected in the GERM-Vet monitoring programme

Abstract: This study showed that the blaCTX-M-1 gene is the predominant ESBL gene among E. coli isolates from diseased animals in Germany and a considerable structural heterogeneity was found in the regions flanking the blaCTX-M-1 gene. Insertion sequences, transposons and recombination events are likely to be involved in alterations of the ESBL gene regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 41 publications
7
38
0
Order By: Relevance
“…16,19,25,37 In this study, only CMY-2 (or SNP variant) was observed, which is also in line with the results observed in clinical samples of companion animals. 19,37 The majority of ESBLs observed here were of CTX-M-1 group and less commonly of CTX-M-9 group with only one TEM-52, a distribution also reported by others.…”
Section: Discussionsupporting
confidence: 91%
“…16,19,25,37 In this study, only CMY-2 (or SNP variant) was observed, which is also in line with the results observed in clinical samples of companion animals. 19,37 The majority of ESBLs observed here were of CTX-M-1 group and less commonly of CTX-M-9 group with only one TEM-52, a distribution also reported by others.…”
Section: Discussionsupporting
confidence: 91%
“…The three ESBL genes detected at the farms are the most commonly observed genes on poultry meat in the Netherlands and are, with the exception of bla SHV-12 , equally common in humans (15 those observed in the current study (15,16,(36)(37)(38)(39)(40) In conventionally kept broilers, the prevalence of ESBL-producing E. coli is very high, with 100% of farms positive (37), and 77 to 94% of all retail chicken meat is contaminated with ESBL-producing E. coli bacteria (15,16). The prevalence in laying hens has not been published yet, but preliminary data suggest 100% positivity in conventionally kept laying hens, as well, albeit at lower concentrations than in broilers (unpublished observations).…”
Section: Discussionmentioning
confidence: 53%
“…The latter two ST types are frequently identified as ESBL-carrying E. coli isolates not only in humans, but also in veterinary fields [32,33,36,37,38]. Notably, of 5 D1-O1-ST648 strains in 212 strains examined in the present study, 3 strains harbored both aac(3)-II and CTX-M-type ESBL genes (table 3), and another D1-O1-ST648 strain harbored the aac(6')-Ib-cr gene and was resistant to AMK.…”
Section: Discussionmentioning
confidence: 99%